Parametric Analysis of Rainfall Variability Over Some Selected Locations in Nigeria - O. A, Falaiye; A. G, Olaitan; S. C, Nwabachili (International Journal of Climate Research, 2021)
Rainfall is one meteorological parameter that affects virtually all human activities. For instance, the amount of rainfall received in an area is an important determining factor in estimating or quantifying the amount of water available to meet various demands, such as agricultural, industrial, domestic water supply, and power generation. Climate change has generally been accepted to be a result of the emission of excess greenhouse gases. It has caused an increase in flooding, severe and more frequent droughts, increase in wildfires, and heatwaves in various parts of the globe. Climate change is said to have a considerable impact on the variability in hydro-meteorological variables such as rainfall, temperature, and evaporation. In this study, we carry out a parametric analysis of rainfall variability over some selected locations in Nigeria and determine the trend using surface observation data from seven weather stations. The datasets of rainfall used in this study were acquired; from the Nigerian Meteorological Agency (NIMET) for a period of 30 years (1980 to 2010) from seven locations; which are Abuja, Enugu, Ikeja, Ilorin, Maiduguri, Port Harcourt, and Sokoto, representing the six geographical zones of Nigeria. The results gotten showed an upward movement in the trend line which indicated an increase in the amount of rainfall received by the study areas. While some Cities (Maiduguri, Sokoto) received a large increase in the amount of rainfall received yearly, others received a slight increase such as Lagos, Port Harcourt, Ilorin, Abuja and Enugu.